Comparative Single-Dose mRNA and ChAdOx1 Vaccine Effectiveness Against Severe Acute Respiratory Syndrome Coronavirus 2, Including Variants of Concern: Test-Negative Design, British Columbia, Canada . (27th January 2022) - Skowronski, Danuta M; Setayeshgar, Solmaz; Zou, Macy; Prystajecky, Natalie; Tyson, John R; Sbihi, Hind; Fjell, Chris D; Galanis, Eleni; Naus, Monika; Patrick, David M; El Adam, Shiraz; Ahmed, May A; et al.
Abstract: Background: In British Columbia, Canada, most adults 50–69 years old became eligible for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine in April 2021, with chimpanzee adenoviral vectored vaccine (ChAdOx1) restricted to ≥55-year-olds and second doses deferred ≥6 weeks to optimize single-dose coverage. Methods: Among adults 50–69 years old, single-dose messenger RNA (mRNA) and ChAdOx1 vaccine effectiveness (VE) against SARS-CoV-2 infection and hospitalization, including variant-specific, was assessed by test-negative design between 4 April and 2 October 2021. Results: Single-dose VE included 11 861 cases and 99 544 controls. Median of postvaccination follow-up was 32 days (interquartile range, 15–52 days). Alpha, Gamma, and Delta variants comprised 23%, 18%, and 56%, respectively, of genetically characterized viruses. At 21–55 days postvaccination, single-dose mRNA and ChAdOx1 VE (95% confidence interval [CI]) was 74% (71%–76%) and 59% (53%–65%) against any infection and 86% (80%–90%) and 94% (85%–97%) against hospitalization, respectively. VE (95% CI) was similar against Alpha and Gamma infections for mRNA (80% [76%–84%] and 80% [75%–84%], respectively) and ChAdOx1 (69% [60%–76%] and 66% [56%–73%], respectively). mRNA VE was lower at 63% (95% CI, 56%–69%) against Delta but 85% (95% CI, 71%–92%) against Delta-associated hospitalization (nonestimable for ChAdOx1). Conclusions: A single mRNA or ChAdOx1 vaccine dose gave important protection against SARS-CoV-2, including early variants of concern. ChAdOx1 VE was lower against infection, but 1 dose of either vaccine reduced the hospitalization risk by >85% to at least 8 weeks postvaccination. Findings inform program options, including longer dosing intervals. Abstract : Test-negative design among adults aged 50–69 years in British Columbia shows that 1 dose of mRNA vaccine was more effective than ChAdOx1 against SARS-CoV-2 infection, but 1 dose of either vaccine reduced the hospitalization risk by >85% to at least 8 weeks postvaccination.